In vivo Microbiome Profiling of the Luminal and Mucosal Surface of the Duodenum Using a Cannulated Yearling Bovine Model - Stockler, Ricardo M.; Higgins, Keah V.; Hallowell, Haley; Groover, Erin S.; Hiltbold, Elizabeth M.; Newcomer, Benjamin W.; Walz, Paul H. (Frontiers in Veterinary Science, 2020)
The gut microbiome provides important metabolic functions for the host animal. Bacterial dysbiosis as a result of bacterial, viral, and parasitic gastrointestinal infections can adversely affect the metabolism, productivity, and overall health. The objective of this study is to characterize the commensal microbiome present in the lumen and the mucosal surface of the duodenum of cattle, as we hypothesize that due to metabolic processes and or host proprieties, there are differences in the natural microbiota present in the mucosal surface and luminal contents of the bovine duodenum. Duodenal lumen contents and mucosal biopsies were collected from 6 dairy crossbred yearling steers. A flexible video-endoscope was used to harvest biopsy samples via a T shaped intestinal cannula. In order to assess as much environmental and individual steer microbiota variation as possible, each animal was sampled three times over a six week period. The DNA was extracted from the samples and submitted for16S rRNA gene Ion Torrent PGM bacterial sequencing. A detailed descriptive analysis from phylum to genus taxonomic level was reported. Differences in the microbiome population between two different sites within the duodenum were successfully characterized. A great and significant microbiota diversity was found between the luminal and mucosal biopsy. At the phylum taxonomic level, Firmicutes and Bacteroidetes composed over 80% of the microbiome. Further analysis at lower taxonomic levels, class, family and genus, showed distinct diversity and distribution of the microbiome. Characterizing the gastrointestinal microbiome in vivo is imperative. The novelty of this study is the use of live cattle undergoing customary husbandry allowing real-time analysis of the duodenum microbiome contributing to the literature with respect to the bovine duodenum microbiome.